Perbezaan kemahiran pemikiran kritikal mahasiswa/mahasiswi yang menyertai ekspedisi pendakian - Mustafa, Munauwar; Ismail, Mohd Azril; Badlishah, Shahrizal (Akademia Baru, 2016)
This study aims to investigate the significant elements that predict profitability behavior of Islamic banks within the composition of cost efficiency.It is not clear whether Islamic banks can simultaneously achieve higher profitability with cost efficiency.The result of the first model in this study found all predicting variables are significantly explaining profitability after robust standard errors of fixed effect model. Also, the interaction between cost efficiency and bank activities within each country’s macroeconomic environment presents an attractive outcome of expense preference behavior.The paper advocated for prioritization of cost efficiency which has the tendencies of attaining both utilization of available resources and higher returns to satisfy all the stakeholders.